Morfometria do núcleo de células neoplásicas como método de diagnóstico de Histiocitoma, Mastocitoma e tumor venéreo transmissível em cães - Waldemarin, Katia Cristina de Andrade (2003)
Histiocytoma, mastocytoma and transmissible venereal tumors are frequent in dogs. The differential diagnostic between these tumors is important, mainly when the transmissible venereal tumor is ectopic. Image cytometry can be used as an auxiliary tool in the differential diagnostic of the histological similar pathology, such as these tumors. The objective of this work was to characterize the nucleaus and the chromatin morphometry of the neoplasic cells of these tumor types and to evaluate the potential of this methodology as differential diagnostic of these pathologies. Fifteen histological slides of each type of the tumor were used and one hundred nucleus of each case were analyzed. Geometric basic characteristics (area, perimeter and ellipticity) traditionally used as auxiliary tools in the histopathological diagnostic, as well as more elaborated geometric measures and the characterization of the nuclear texture through of lacunarity and others methods considered in this work were used Variance and canonical discriminant analysis were made for statistic evaluation. The morphometry using basic measurements was inefficient to identify correctly these tumor types. However, this methodology showed to be a good tool for differential diagnosis of the histiocytoma and transmissible venereal tumor. This methodology should be used only as an auxiliary tool for the differential diagnostic of the three considered tumor types